PENGARUH DISTANCE LEARNING TERHADAP HASIL BELAJAR APPROACH AND AREA CONTROL PROCEDURES TARUNA PRODI LLU POLITEKNIK PENERBANGAN SURABAYA - Sudrajat Sudrajat; Meita Maharani Sukma; Wasito Utomo; Julfansyah Margolang (Jurnal Penelitian, 2023)
This research is a quasi-experimental research with a quantitative descriptive research approach, which aims to: (1) To determine the difference in the results of Practicum Learning conducted online with direct practicum in the APP Laboratory at D3 LLU XII cadets of Aviation Polytechnic Surabaya (2) To determine the effect of distance learning Aproach and Area Control Procedures for the motivation and learning outcomes of D3 LLU XII cadets of Aviation Polytechnic Surabaya (3) To find out the causal relationship between practical teaching methods in the laboratory and online practicums on the learning outcomes of D3 LLU XII cadets.The results obtained are that there is an influence of the distance learning method on the cadets' learning outcomes in the Approach Control Procedural course which includes planning, implementation, results and evaluation. The conclusions of this study are (1) LLU XII cadets in the planning and preparing category have a high average, namely in the category of determining the preparation of learning to be used, the percentage is 73% and the category feels they have the responsibility to attend learning, the percentage is 54%, (2 ) LLU XII cadets in the implementation category have a high average, namely in the category of implementing strategies in exercise according to each learning style, the percentage is 57% and the habit category for supporting and overcoming problems in learning gets a percentage of 60% (3) LLU XII cadets in the Outcomes and Evaluation categories, the average percentage is high, namely in the Habits After Finishing Learning category, a high percentage of 67% is obtained and the self-evaluation category for learning outcomes has a balanced percentage in the high and medium categories, namely 50% versus 50%.